2023
DOI: 10.18697/ajfand.117.21970
|View full text |Cite
|
Sign up to set email alerts
|

The subak-based agro-tourism management model in the world cultural heritage area of Catur Angga Batukaru Tabanan Regency, Bali province, Indonesia

Abstract: When it was designated as a World Cultural Heritage (WCH) in 2012, there were 14 Subak organizations formed in Catur Angga Batukaru Area. However, it seems that only Subak Jatiluwih has the privilege to experience rapid development as a tourism destination. The other 13 Subak area in Catur Angga Batukaru has not been well developed. The beauty of their rice terraces, plantation fields, temples and rivers has not been appropriately exposed to the tourists. Further studies are required to investigate the potenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Therefore, waste must be appropriately managed not to disturb or threaten public health as little as possible. Good waste management is not only for the benefit of health but also for the beauty of the environment in agro-ecotourism areas [87].…”
Section: Sustainability Status Of the Environmental Dimensionmentioning
confidence: 99%
“…Therefore, waste must be appropriately managed not to disturb or threaten public health as little as possible. Good waste management is not only for the benefit of health but also for the beauty of the environment in agro-ecotourism areas [87].…”
Section: Sustainability Status Of the Environmental Dimensionmentioning
confidence: 99%
“…May et al (2019) stated that this policy was also concluded to have a positive impact on farmer regeneration. The limited availability of agricultural labor and harvesting support facilities means that the role of buyers with an assessment system is very much needed by farmers because farmers do not need to pay harvest costs or labor costs (Suamba et al 2023). This system is considered practical because farmers get their production results in the form of money directly.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the environmental services provided by the Subak rice fields to protect soil fertility from erosion has not been widely studied in Bali. The previous research placed more emphasis on studying soil fertility, mapping and the socio-demographics conditions of Subak [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%